PENGARUH PENGELUARAN PEMERINTAH DAERAH TERHADAP PERTUMBUHAN EKONOMI SOLO RAYA 2009-2018 - Fernaldi Anggadha Ratno (JABE (Journal of Applied Business and Economic), 2020)
This quantitative dynamic panel research is aimed to find out the effect of Government Expenditure in forms of Local Government Expenditure towards the Economic Growth of Solo Raya in 2009-2018. The analysis uses autoregressive distributed-lag dynamic model which includes not only the current but also the lagged values of the explanatory variable, and one or more lagged values of the dependent variables. The result of the analysis shows that Direct Expenditure gives more 1.32E-07 percent significant effect to the Economic Growth in Solo Raya, so does the Economic Growth of the past one year. Both Direct and Indirect Expenditure of the past one year give additional effects to the Economic Growth. Based on the analysis, it is recommended for the government to more thoroughly and carefully count the number of government expenditures and pays more attention to the allocation of Direct Expenditure which is able to contribute and give significant effect to the economic growth of a region.